Relationship between Head of Ward’s Actuating Function and Spiritual Nursing Care - Sunardi; Tri Kurniati; Giri Widakdo (NERS Jurnal Keperawatan, 2025)
Head of ward has a role to direct and motivate nurses especially in spiritual care implementation. This study aimed to identify the relationship between head nurse’s actuating function and spiritual nursing care implementation at Gedung A RSUPN Dr Cipto Mangunkusumo. This study used cross sectional design with 153 respondents included. Data was collected using questionnaires and then analyzed using Chi Square test and multiple logistic regression.  The result showed that there was significant relationship between head nurse’s actuating function and spiritual nursing care implementation (p value 0.000, OR 5.814). Great direction from head nurse with a high actuating function has a 5.8 times chance of implementing spiritually based nursing care compared to one with a low level of carrying out the actuating function. The nursing and training sector can develop training programs for spiritual nursing care, monitoring and evaluation, and supervision of its implementation.